Dampak Lingkungan Dan Pergaulan Terhadap Perkembangan Karakter Siswa dalam Pendidikan Karakter - Marzuki, Marzuki (Jurnal Al-Kifayah: Ilmu Tarbiyah dan Keguruan, 2025)
Amidst the rapid globalization and digital technological advancements, character education has become an urgent necessity to shape a generation that excels not only academically but also morally. This study aims to analyze the influence of family environment, peer interactions, and digital technology on students’ character development within the context of modern Islamic education. This research employed a qualitative approach with a case study design conducted at MTs Negeri 1 Kebumen. Data were collected through in-depth interviews, observations, and documentation, and analyzed using thematic analysis with data triangulation to ensure validity. The findings reveal that the family environment plays a dominant role in shaping students’ religious character, while peer relationships and digital technology significantly affect their social and moral behavior. Strengthening Islamic values through faith-based school programs and family guidance effectively helps students utilize technology wisely. The study implies that collaboration among families, schools, and communities is essential in developing an Islamic character education ecosystem that adapts to the challenges of the digital era